Un restauro creativo. 1972 Pierluigi Spadolini e la sede storica del Monte dei Paschi di Siena - Fabbrizzi, Fabio (Firenze Architettura, 2018)
In the vast and varied work of Pierluigi Spadolini, the so-called “creative restoration” incarnates the specific, and perhaps most successful field of application of all his recurring themes. The dialogue and confrontation with the pre-exisiting conditions, in fact, seem to give space to that balance between rationality and organicism that is so vigorously present in his language, often marked by the mediation between plasticity and syntax.